2013
DOI: 10.1080/00222348.2013.808522
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Crystallization of Linear Polyethylene in Blends with Isotactic Polypropylene

Abstract: The structure and morphology of extrusion oriented ribbons of polypropylene / polyethylene blends is described. The blends with 20, 30 and 40% of oriented isotactic polypropylene fibrils show homo-and hetero-epitaxial structures. Partial mutual solubility of the blend components influenced the melting and crystallization behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Thus, it can be already stated that there is a certain nucleating effect toward HDPE in the presence of PPn domains, while this effect is absent in the presence of PPp domains. A similar effect was already reported by Last in blends of low-density PE and PP, and by Rybnikar and Kaszonyiova for binary blends of linear PE and PP as major and minor components, respectively. Furthermore, in the work of Zhang and Ajji, a nucleating effect toward the PE phase at the interface in blends of LLDPE and PP was found and related to the difference in T c between LLDPE and the type of PP used.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, it can be already stated that there is a certain nucleating effect toward HDPE in the presence of PPn domains, while this effect is absent in the presence of PPp domains. A similar effect was already reported by Last in blends of low-density PE and PP, and by Rybnikar and Kaszonyiova for binary blends of linear PE and PP as major and minor components, respectively. Furthermore, in the work of Zhang and Ajji, a nucleating effect toward the PE phase at the interface in blends of LLDPE and PP was found and related to the difference in T c between LLDPE and the type of PP used.…”
Section: Resultssupporting
confidence: 88%
“…1.7 °C was detected between the T c of neat and the T c of blended PPn. In previous studies, this effect of PE on the crystallization kinetics of PP, when melt-blended, was reported and explained as either a diluent effect of the PE phase (still molten at the temperatures at which PP crystallizes) on the crystallizing PP phase 7,13 or as a decrease in the number of heterogeneous nuclei in the PP phase due to their migration toward PE domains. 10,60 However, the first hypothesis seems not appropriate to explain this phenomenon for the present case study.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that in compatibilized PP/PET microfibrillated composites, the aspect ratio of microfibrils and mechanical properties improves only up to an optimum amount, above which the properties are not only not enhanced, but are actually diminished. ,, …”
Section: Resultsmentioning
confidence: 99%